Analysis Of The Factors That Affect The Productivity Of Rattan Furniture Craftsmen In The Village Trangsan Kartasura District Sukoharjo Regency - Suwarto, Suwarto, Drs. M. Farid Wajdi, MM., Ph.D, Drs. Syamsudin, M.M (2015)
This research is about salary and work experience influences concerning productivity of rattan furniture craftspeople in Trangsan village, Gatak sub district Sukoharjo district has been was worked by 62 of 70 craftspeople. This is research as regard problems in the salary and work experience and their productivity of producing furniture. From the analyze data that was carried on showed that instrument validity test on variable that as salary (X1) and work experience (X2) concerning limited variable that as craftspeople productivity (Y) in Trangsan village of Sukoharjo has showed valid value where were each salary, experience and productivity variables rcount > rtable or rcount > 0,250, whereas reliability test on variables of salary, work experience and productivity showed reliable value where were crombach's alpha salary 0,767) work experience (0,782) and work productivity (0,721) each > the value of critical (0,70) whereas the resulof classical assumption test for each variables, showed that all of variables was qualified test, consists of multi co-linearity, autocorrelation, heteroskedasitas and normality. For analyze of bifilar linier regression, after known the constant number (a) and regression coefficient each variable (b1 and b2), so the regression equation as Y = 5,280 + 0,336 X1 + 0,366 X2. From this analyze, so the variable that influence dominant concerning craftspeople productivity in Tragan village of Sukoharjo is work experience (X2) because the value of regression coefficient is biggest as 0,366. Significant of salary influence (X1) concerning craftspeople productivity in Tragan village of Sukoharjo has obtained probability value as many 0,003 < 0,05 so Ho was refused that mean there were significant of salary (X1) concerning craftspeople productivity (Y) in Trangsan village of Sukoharjo. Whereas significant test of experience work (X2) concerning craftspeople productivity the probability as many 0,000 < 0,05 so Ho was refused that mean there were significant influence of work experience (X2) in Tragan village of Sukoharjo. For the model constant test was obtained probability value as many 0,000 < 0,05 so Ho was refused that mean the model was used to test the free variable influence as salary (X2) concerning craftspeople productivity limited variable that as craftspeople productivity (Y) in Trangsan village of sukoharjo was correct. The result of determination coefficient was obtained Adjusted R Square value = 0,594 that mean known influence was given by free variable that as salary (X1) and wor experience (X2) concerning limited variable that as craftspeople productivity in Trangsan village of Sukoharjo 59,4% and the other else (100%- 59,4%=40,0% influenced by the else factors example discipline, safety, security and the other else.